Sensory Evaluation and Fiber Content Analysis of Analog Rice with Moringa Leaf Flour Substitution - Ika Wahyuningsih; Arif Sabta Aji; Veriani Aprilia; Satrijo Saloko; Dina Seftina; Vivi Meiliza Majid (Indonesian Journal of Human Nutrition, 2023)
Analog rice, also known as artificial rice, is a rice substitute made from a combination of local flours, including sorghum flour, mocaf flour, and glucomannan. Incorporating Moringa leaves into analog rice flour offers potential health benefits due to its anti-diabetic and antihyperglycemic effects, which lowers blood sugar levels and HbA1C levels in individuals with Diabetes Mellitus. This study aims to develop analog rice using a combination of sorghum, mocaf, and glucomannan flour and to determine its sensory properties and fiber content. This study employed an experimental design, with Moringa leaf flour substitutions divided into P1 (0%), P2 (2%), P3 (4%), P4 (6%), P5 (8%), and P6 (10%), using a Completely Randomized Design (CRD). Sensory evaluation was done using the hedonic test, involving 25 trained panelists who assessed taste, aroma, color, and texture. Fiber content was analyzed using the enzymatic gravimetric test. Data were analyzed using a one-way ANOVA test, followed by Duncan’s test if p<0.005. The results showed a significant effect of Moringa leaf flour substitution on sensory evaluation and fiber content (p<0.001 for all comparisons). Based on sensory evaluation, panelists preferred analog rice P2 (2%). The fiber content of analog rice with Moringa leaf flour substitution ranged from 11.16 to 13.65% for insoluble dietary fiber, 0.60 to 0.99% for soluble dietary fiber, and 11.80 to 14.62% for total dietary fiber. Moringa leaf flour substitution had a significant difference in sensory evaluation and fiber content of analog rice. The highest preference level was found in P2 (2%) analog rice, while the highest total fiber content was found in P5 (8%) analog rice.